PANCARAGAM AS AN ALTERNATIVE OF CULTURAL MUSIC CULTURE IN PAUAH AND KURANJI PADANG REGIONS - HAFIF HR (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2020)
Celebratory music has become a tradition in society. Almost all regions in Nusantara have a form and kind of music that used as a procession, whether in a wedding or other cultural ceremony. In Minangkabau, celebratory music as a tradition is taking a kind of music named Talempong Pacik, using talempong, sarunai, pupuik batang padi, gendang sarunani, and gendang tambua. In Pauah and Kuranji, celebratory music is also has a function as entertainment music that develops in the society called Pancaragam. The presence of this music is background by military ceremony music and then developed into entertainment music as well as being used as a procession music using conventional brass instruments such as trumpets, saxophone, and trombone also percussion instruments such as cymbal, snare drum, and bass drum. The presence of Pancaragam music in Pauah and Kuranji has give manifest function or real function, objective consequences that gave contribution in adjustment or adaptation of the system that desired and realized by the participants of the system. The existence of Pancaragam as an alternative for society is used in ceremony and serves as entertainment in wedding ceremony. Until now, Pancaragam is still used by the society in Pauah and Kuranji as an alternative ceremony music culture and also as an entertainment in wedding ceremony.